A novel HLA‐A allele, A*24:02:17, identified by sequence‐based typing. Issue 2 (29th December 2012) - Liu, N.; Zhang, Z.; Shan, X.; Ni, L.; Wang, L.
<x xml:space="preserve">Abstract</x> The A*24:02:17 allele differs from the most close matching allele A*24:02:01:01 by one nucleotide substitution in exon 2, at position 264.